PELATIHAN BANTUAN HIDUP DASAR (BHD) BAGI KADER KESEHATAN DI WILAYAH KERJA PUSKESMAS KECAMATAN DARUL IMARAH ACEH BESAR - Afni Yan Syah; Cut Rahmiati; Eri Riana Pertiwi; Nenty Septiana; Novi Afrianti; Ratna Juwita; Wiwin Haryati; Dewi yuliana; Juliana Juliana (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2021)
Background: The National Disaster Management Agency noted that in the period of 2020 there have been 2,925 natural disasters. Aceh is a province that is prone to disasters such as being prone to flash floods, landslides, and earthquakes. This series of natural phenomena has made the people of Aceh familiar with various disasters. One of the ways to prevent the number of victims in a disaster is to have volunteers around the community, namely health cadres. Health cadres are trained as monitors, reminders and advocates to promote health so that it is possible for cadres to have the ability to perform basic life support in the event of an emergency. Purpose: to increase the knowledge and skills of health cadres about BHD training in the community during an emergency. Methods: BHD training activities are carried out for cadres who have not received training. Socialization to cadres about BHD through lectures, questions and answers, and demonstrations using Phantom BHD. The activity was carried out in 3 sessions with the details of the activities. They were pretest activity in the form of filling out questionnaires by the participants, providing material on BHD that must be accepted by cadres, and posttest on the knowledge and understanding of cadres about material that has been given. Results: The results obtained were an increase in the knowledge of cadres from a low level of knowledge of 5.7% to a high level of 68.6%. This shows that there is a change in the level of knowledge and understanding of cadres about basic life support. Conclusion: After this community service, the ability of cadres to carry out basic life support increases so that it is expected to increase life expectancy in the community in the event of an emergency